HIV risk-related sexual behavior by cohabiting partner status among factory workers: Results from the 2015 Bangkok behavioral surveillance survey (BSS) - Hong, Seo Ah (Cogent social sciences, 2017)
This study aimed to determine the prevalence of HIV risk-related sexual behaviors in the past 12 months and their related factors by cohabiting partner status among factory workers in Bangkok, one of the higher AIDS disease-burden provinces. The study found that one in five factory workers engaged in at least one of three HIV risk-related sexual behaviors, including ever-sex and unprotected-sex with a non-regular partner and multiple sexual partners. Those without a cohabiting partner (52%) were 4-fold greater than those with a cohabiting partner (13%). Factors associated with sexual risk behavior include being male, being younger, and having had HIV risk-related sexual behavior at first sex, regardless of cohabiting partner status (despite positive association with frequent alcohol consumption for those without a cohabiting partner). These findings imply the need for promotion of condom use in all episodes of sex with a potentially risk partner, reduction of non-regular partner sex and provision of education for safe sex for Bangkok factory workers.